2013
DOI: 10.1155/2013/738257
|View full text |Cite|
|
Sign up to set email alerts
|

Hox Targets and Cellular Functions

Abstract: Hox genes are a group of genes that specify structures along the anteroposterior axis in bilaterians. Although in many cases they do so by modifying a homologous structure with a different (or no) Hox input, there are also examples of Hox genes constructing new organs with no homology in other regions of the body. Hox genes determine structures though the regulation of targets implementing cellular functions and by coordinating cell behavior. The genetic organization to construct or modify a certain organ invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 305 publications
(451 reference statements)
0
23
0
2
Order By: Relevance
“…The cellular side of Hox activity Recent reviews have summarised the many different cellular functions controlled by Hox proteins, including changes in cell shape and migration, proliferation or programmed cell death and differentiation (Cerdá-Esteban and Spagnoli, 2014;Philippidou and Dasen, 2013;Sanchez-Herrero, 2013;Shah and Sukumar, 2010;Taniguchi, 2014). Here, we review phenotypes associated with Hox gene dysfunction/manipulation that provide insights, at least at the phenomenological level, into how Hox genes achieve their functions.…”
Section: An Overview Of the Hox Gene Familymentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular side of Hox activity Recent reviews have summarised the many different cellular functions controlled by Hox proteins, including changes in cell shape and migration, proliferation or programmed cell death and differentiation (Cerdá-Esteban and Spagnoli, 2014;Philippidou and Dasen, 2013;Sanchez-Herrero, 2013;Shah and Sukumar, 2010;Taniguchi, 2014). Here, we review phenotypes associated with Hox gene dysfunction/manipulation that provide insights, at least at the phenomenological level, into how Hox genes achieve their functions.…”
Section: An Overview Of the Hox Gene Familymentioning
confidence: 99%
“…For example, initial studies recognised the patterning functions of Hox genes, showing that they provide axial positional information and contribute to defining cellular territories and establishing boundaries. More recent work showed that Hox genes also provide contributions to organogenesis per se (Hombria and Lovegrove, 2003) through the control of a variety of cellular functions including differentiation, proliferation, migration or death (Sanchez-Herrero, 2013). Although various molecular functions have been attributed to Hox proteins, including non-transcriptional functions such as replication and translation (Miotto and Graba, 2010;Rezsohazy, 2014) (Box 1), Hox proteins are best known as transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of vertebrate hematopoiesis that has not been mirrored in Drosophila is the role of Hox genes. Hox genes are well known for their conserved role in body axis formation across all bilaterians [25], but also play roles in vertebrate hematopoiesis [26], autophagy [27], as well as cell proliferation, differentiation, migration and apoptosis [28]. Hox genes are transcribed in HSCs as well as lineage progenitors, while being suppressed in differentiated blood cells [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of vertebrate hematopoiesis that has not been mirrored in Drosophila is the role of Hox genes. Hox genes are well known for their conserved role in body axis formation across all bilaterians 5 27 , but also play roles in vertebrate hematopoiesis 28 , autophagy 29 , as well as cell proliferation, differentiation, migration and apoptosis 30 . Hox genes are transcribed in HSCs as well as lineage progenitors, and are suppressed in differentiated blood cells [31][32][33][34][35] Overexpression models show blockages in certain stages of development, expansion of HSCs, the circulation of blast cells, etc.…”
mentioning
confidence: 99%